1979
DOI: 10.1029/jc084ic11p06961
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric implications of studies of Central American volcanic eruption clouds

Abstract: During February 1978 a group of scientists from the National Center for Atmospheric Research, several colleges and universities, the U.S. Geological Survey, and NASA used a specially equipped Beech Queen Air aircraft to make 11 sampling flights in Guatemala through the eruption clouds from the volcanoes Pacaya, Fuego, and Santiguito. Measurements were made of SO42−, SO2, HCl, HF, and 11 cations that were in water‐soluble form, on samples collected by a specially designed filter pack. Particle size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Previous aerosol studies identified some of the metal bearing phases (Cadle et al, 1979;Rose et al, 1982;Hobbs et al, 1982;Mackinnon et al, 1984;Varekamp et al, 1986;Symonds and Reed, 1993;Toutain et al, 1995;Galindo et al, 1998) but could not provide information on the temperatures or conditions of the aerosols formation. Other solid phases probably present in the plumes might not be identified in the collected aerosols because of their low concentration or because of the small size of the particles (<1 μm).…”
Section: Discussionmentioning
confidence: 99%
“…Previous aerosol studies identified some of the metal bearing phases (Cadle et al, 1979;Rose et al, 1982;Hobbs et al, 1982;Mackinnon et al, 1984;Varekamp et al, 1986;Symonds and Reed, 1993;Toutain et al, 1995;Galindo et al, 1998) but could not provide information on the temperatures or conditions of the aerosols formation. Other solid phases probably present in the plumes might not be identified in the collected aerosols because of their low concentration or because of the small size of the particles (<1 μm).…”
Section: Discussionmentioning
confidence: 99%
“…Direct sampling of high temperature fumaroles represent compositions of gases derived from quiescent magma (Giggenbach, 1996;Fischer et al, 1997Fischer et al, , 1998; however, these compositions are variably affected by hydrothermal processes and direct sampling is impossible during explosive eruptions. Filter sampling of gases and particles from plumes provides information on eruptive gas compositions and plume processes and has led to the identification of sulfate and chloride salts and sulfuric acid aerosols as common products in the plume (Cadle et al, 1979;Smith et al, 1982;Casadevall et al, 1984;Rose et al, 1988Rose et al, , 2006. It has been estimated that $30% of the total emitted S can be scavenged from plumes by adsorption as sulfates onto ash, which is deposited (Rose, 1977;Varekamp et al, 1984;de Hoog et al, 2001a).…”
Section: Introductionmentioning
confidence: 96%
“…Despite some conjectures about the possible injection of hydrogen fluoride into the atmosphere by strong volcanic eruptions (Cadle et al, 1979), HF has no known significant sources in the troposphere, where its natural background concentration has been poorly monitored but appears to be very low (Cicerone, 1981).…”
Section: Introductionmentioning
confidence: 99%